2005
DOI: 10.1007/s00417-005-0091-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the lens epithelium with respect to cataractogenesis—light microscopic and Scheimpflug densitometric analysis of the cataractous and the clear lens of diabetics and non-diabetics

Abstract: The lens epithelium is primarily damaged in type II diabetics who develop age-related cataract. This might play an important role in cataract formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 22 publications
0
14
1
4
Order By: Relevance
“…These may be attributed to the elevation of the activities of aldose reductase and sorbitol dehydrogenase, the promotor of polylol pathways [33,34]. Aldose Reductase is contributed to the reduction of development of glucose into sugar alcohol sorbitol, which is then metabolized to fructose by sorbitol dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…These may be attributed to the elevation of the activities of aldose reductase and sorbitol dehydrogenase, the promotor of polylol pathways [33,34]. Aldose Reductase is contributed to the reduction of development of glucose into sugar alcohol sorbitol, which is then metabolized to fructose by sorbitol dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,[8][9][10] Furthermore, Pentacam has a program that can evaluate the opacity of the lens by Scheimpfl ug densitometry. 11 We previously applied this program to the cornea and defi ned an index of corneal opacity that we named central corneal densitometry (CCD), and found that CCD is useful for evaluating corneal clarity after refractive surgery. 12 At the same time, several studies have reported no difference, or only a small systematic (statistical) difference, between ultrasonic pachymetry and noncontact techniques, and a signifi cant linear correlation between noncontact technology pachymetry and ultrasonic pachymetry measurements of postoperative CCT.…”
mentioning
confidence: 99%
“…The Scheimpflug principle 20 has been established in the assessment of lens thickness and densitometry [20][21][22] ; corneal transparency, thickness, and curvature 20,23 ; and anterior chamber depth 19,[24][25][26] as well as in the detection of intraocular lens (IOL) tilting. 27 An advantage of the Pentacam rotating Scheimpflug camera is its ability to evaluate the entire anterior eye segment, from the anterior corneal surface to the posterior lens surface, in a single scan without contact with the cornea.…”
mentioning
confidence: 99%